2020
DOI: 10.3390/batteries6010011
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Single-Ion Conducting Polymer Gel Electrolytes for Sodium, Potassium, and Calcium Batteries: Influence of Polymer Chemistry, Cation Identity, Charge Density, and Solvent on Conductivity

Abstract: From the standpoint of material diversification and sustainability, the development of so-called “beyond lithium-ion” battery chemistries is important for the future of energy storage. Na, K, and Ca are promising as the basis for battery chemistries in that these elements are highly abundant. Here, a series of single-ion conducting polymer electrolytes (SIPEs) for Na, K, and Ca batteries are synthesized and investigated. The two classes of metal cation neutralized SIPEs compared are crosslinked poly(ethylene g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 60 publications
0
29
0
Order By: Relevance
“…It is noted that the underlying mechanics of our past results regarding cation transport are reproduced here. Previously, we showed that decreasing the network cation solvation capacity, by decreasing the solvation site density, lead to a lower cation‐polymer interaction and a subsequent increase in conductivity [9,19] . This relationship between conductivity and crosslinking macromonomer chemistry extends to divalent cations as well as monovalent, with the caveat that divalent cations are significantly more difficult for a network to solvate.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…It is noted that the underlying mechanics of our past results regarding cation transport are reproduced here. Previously, we showed that decreasing the network cation solvation capacity, by decreasing the solvation site density, lead to a lower cation‐polymer interaction and a subsequent increase in conductivity [9,19] . This relationship between conductivity and crosslinking macromonomer chemistry extends to divalent cations as well as monovalent, with the caveat that divalent cations are significantly more difficult for a network to solvate.…”
Section: Resultsmentioning
confidence: 90%
“…Previously, we showed that decreasing the network cation solvation capacity, by decreasing the solvation site density, lead to a lower cationpolymer interaction and a subsequent increase in conductivity. [9,19] This relationship between conductivity and crosslinking macromonomer chemistry extends to divalent cations as well as monovalent, with the caveat that divalent cations are significantly more difficult for a network to solvate. Here, the same result is achieved by lowering the solvation capacity via decreased solvation site strength.…”
Section: Passive Polysulfide Absorptionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 This has inspired analogous calcium electrolytes which use common carbonate-4-6 or ether-7 based solvents and predominately ether-based polymer backbones, 8-10 with ionic moieties being one exception. [11][12][13] In the case of polymer electrolytes, however, ether-containing backbones result in low ionic…”
mentioning
confidence: 99%
“…Followed by this, Ford and coworkers 13 were the first to report a gel-type single-ion conducting polymer for calcium ion conduction. We note that since the anions are covalently tethered to the polymer chains in single-ion conducting polymers, they do not partake in ion transport.…”
mentioning
confidence: 99%